Effect of Investment Climate on Small and Medium Scale Enterprises Growth in Makurdi Metropolis, Benue State Nigeria - Garba, Adamu (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2019)
This study evaluated the effect of investment climate on Small and Medium Scale Enterprises growth in Makurdi Metropolis. The study was anchored on The Neoclassical Approach, Financial Growth Theory and Theory of diffusion of innovation. The researcher used both primary and secondary sources from a sample of 250 respondents obtained by the use of a well structured questionnaire from the study areas. The demographic data collected were analyzed using descriptive statistics such as frequency, simple percentage and the relationship between the variables of the study were analyzed using multiple linear regression analysis. The hypotheses of the study were tested using the probability value of the estimates. The result of the regression analysis indicates that a negative relationship exist between access to credit (ACTC) and Small and Medium Scale Enterprises growth in Makurdi Metropolis Nigeria (SGT) and the relationship is not statistically significant (p>0.05) and not in line with a priori expectation. Power supply (PWSP) was positively related to Small and Medium Scale Enterprises Growth in Makurdi Metropolis Nigeria (SGT) and the relationship is statistically significant (p<0.05) and in line with a priori expectation. A positive relationship exist between Information and Communication Technology (ICT) and Small and Medium Scale Enterprises Growth in Makurdi Metropolis Nigeria (SGT) and the relationship is statistically significant (p<0.05) and in line with a priori expectation. It was concluded that for this growth to be achieved, the climate of investment must be addressed and made favourable for business start-up and growth. It was recommended that government should effectively regulate the power sector as there are still lingering challenges with billings, tariffs and metering processes after privatization. To ameliorate the problem faced by SMEs in the study area, government can create hubs for SMEs in the study area and provide them with adequate electricity or develop renewable energy such as solar energy to improve entrepreneurs' access and growth.